PENDAPATAN PETANI DAN KEANEKARAGAMAN TANAMAN PADA BERBAGAI POLA USAHA WANATANI DI SUB DAS MINRALENG HULU KABUPATEN MAROS - Muh. Dassir (PERENNIAL, 2007)
The plant diversity using shanon index and the farmer income level were investigated in this study. This information is very important to contribute some improvement of agroforestry pattern related to the farmer welfare and the ecological productivity in upperstream Minraleng Sub Watershed. Results show that the diversity index of mix public forest was higher than the other patterns, eventhough it has a lower contribution compared to paddyfield. Paddyfield and unirigated-land have a higher contribution to farmer income, but they have lower diversity indexes. In contrast, candlenut monoculture and mix garden have higher diversity indexes and lower contribution to farmer income. A plant diversification under candlenut stands and an economical plant intensification on mix garden were needed to increase the farmer income and the diversity of economic plants. Key words: Diversity index, farmer income, agroforestry, Minraleng Sub Watershed References